Photo de-mixing in mixed halide perovskites: the roles of ions and electrons. (1st January 2022) - Wang, Ya-Ru; Yeong Kim, Gee; Kotomin, Eugene; Moia, Davide; Maier, Joachim
Abstract: Mixed halide perovskites have attracted great interest for applications in solar cells, light emitting diodes and other optoelectronic devices due to their tunability of optical properties. However, these mixtures tend to undergo de-mixing into separate phases when exposed to light (photo de-mixing), which compromises their operational reliability in devices. Several models have been proposed to elucidate the origin of the photo de-mixing process, including the contribution of strain, electronic carrier stabilization due to composition dependent electronic energies, and light induced ionic defect formation. In this perspective we discuss these hypotheses and focus on the importance of investigating defect chemical and ion transport aspects in these systems. We discuss possible optoionic effects that can contribute to the driving force of de-mixing and should therefore be considered in the overall energy balance of the process. These effects include the selective self-trapping of photo-generated holes as well as scenarios involving multiple defects. This perspective provides new insights into the origin of photo de-mixing from a defect chemistry point of view, raising open questions and opportunities related to the phase behavior of mixed halide perovskites.